Prenatal and perinatal factors influencing nociception, addiction and behavior during ontogenetic development - Rokyta, Richard; Yamamotová, Anna; Šlamberová, Romana; Franěk, Miloslav; Vaculín, Šimon; Hrubá, Lenka; Schutová, Barbora; Pometlová, Marie (Physiological research, 2008)
This review, which summarizes our findings concerning the long-term effects of pre-, peri- and postnatal factors affecting development, nociception and sensorimotor functions, focuses on three areas: 1) perinatal factors influencing nociception in adult rats were examined in rats with hippocampal lesions, after the administration of stress influencing and psychostimulant drugs (dexamethasone, indomethacine and methamphetamine); 2) the effect of pre- and early postnatal methamphetamine administration was shown to impair the development of sensorimotor functions tested in rat pups throughout the preweaning period; 3) the effect of extensive dorsal rhizotomy of the brachial plexus during the early postnatal period was studied with respect to neuropathic pain development and sensorimotor functions. The present study indicates that prenatal or neonatal stress, as well as various drugs, may disturb the development of the nociceptive system and cause long-term behavioral changes persisting to adulthood and that some types of neuropathic pain cannot be induced during the first two postnatal weeks at all. A mature nervous system is required for the development of the described pathological behaviors.
Keywords: methamfetamin; Animals; Stress, Physiological; novorozená zvířata; Methamphetamine; Female; návykové chování; ženské pohlaví; indomethacin; Animals, Newborn; Indomethacin; lidé; chování zvířat; nervový systém; těhotenství; Behavior, Addictive; zpožděný efekt prenatální expozice; Maternal Behavior; fyziologický stres; Psychotropic Drugs; bolest; Male; Nervous System; dexamethason; psychotropní léky; Dexamethasone; Prenatal Exposure Delayed Effects; krysa rodu Rattus; Behavior, Animal; Pain; mateřské chování; zvířata; mužské pohlaví; Pregnancy; Rats; Humans